Plasma Glycoprotein Efflux Induced Resistance: Implications, Mechanism, Inhibitors, and Novel Strategies to Overcome - Sureshkumar, Raman (Asian Journal of Pharmaceutics (AJP), 2018)
This review aims at the drug-resistant factors, its effects, and methods to overcome. P-glycoprotein (P-gp) is an energy-dependent efflux transporter which plays a leading role in multidrug resistance (MDR) of the majority of drugs and is involved in the efflux of toxins, xenobiotics, and drugs out of the body. Their unique mechanism of action put them in the spotlight for the drug discovery process. Modification of drug transporters through inhibitors, inducers or the methods of genetic polymorphism are being used recently. Uses of specific inhibitors or blockers with a parent drug have been evolved as a new method to alter MDR. These inhibitors are classified into various generations based on the properties that they exhibit. MDR is a significant obstacle resulting from the overexpression of some proteins like P-gp which reduces therapeutic efficacy of various drugs associated with cancer, tuberculosis, malaria, and human immunodeficiency virus, etc. Inhibitors of P-gp can be regarded as an explicit remedy for this puzzling condition. Although various chemical inhibitors had been developed, natural agents are comparatively safer than synthetic or semi-synthetic agents. Novel strategies and formulations are developed to alter the expression of P-gp is also mentioned in this paper.